The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1089/neu.2013.3286
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Traumatic Brain Injury Alters Ethanol Consumption and Sensitivity

Abstract: Altered alcohol consumption patterns after traumatic brain injury (TBI) can lead to significant impairments in TBI recovery. Few preclinical models have been used to examine alcohol use across distinct phases of the post-injury period, leaving mechanistic questions unanswered. To address this, the aim of this study was to describe the histological and behavioral outcomes of a noncontusive closed-head TBI in the mouse, after which sensitivity to and consumption of alcohol were quantified, in addition to dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 66 publications
5
40
1
Order By: Relevance
“…Following our recent publication 4 , we now present the first volumetric analysis of NAc after experimental TBI, showing both astrocyte and microglial activation (Figure 1B and 1C) and the upregulation of numerous immune response genes post-injury (Figure 3). Our studies are in agreement with other investigations where the presence of increased reactive astrocytes (evaluated by elevated GFAP expression) can be seen in the NAc in both blast and closed head injury models of TBI 36, 37 . These studies have also identified upregulation of apoptotic markers in the NAc, suggesting that TBI may cause neuronal cell death in regions of the brain that mediate drug abuse behavior 37 .…”
Section: Discussionsupporting
confidence: 93%
“…Following our recent publication 4 , we now present the first volumetric analysis of NAc after experimental TBI, showing both astrocyte and microglial activation (Figure 1B and 1C) and the upregulation of numerous immune response genes post-injury (Figure 3). Our studies are in agreement with other investigations where the presence of increased reactive astrocytes (evaluated by elevated GFAP expression) can be seen in the NAc in both blast and closed head injury models of TBI 36, 37 . These studies have also identified upregulation of apoptotic markers in the NAc, suggesting that TBI may cause neuronal cell death in regions of the brain that mediate drug abuse behavior 37 .…”
Section: Discussionsupporting
confidence: 93%
“…CCI also did not affect locomotor activity, time in the open arms of the elevated plus maze (a measure of anxiety), or gross brain anatomy in ventral brain regions involved in fear circuitry. These findings suggest that our published model of CCI (Yang et al, 2010) does not affect the neural mechanisms of fear and extinction within the first two weeks of injury, which represents the early phase of injury (Lowing et al, 2014). …”
Section: Discussionmentioning
confidence: 73%
“…8,9 There also is mounting clinical and experimental evidence that TBI increases problem alcohol intake. [9][10][11][12] Problem drinking also greatly increases the chances for additional TBI later in life, which can produce much greater impairments in previously injured patients. 4 Children who suffer TBI are less likely to complete their education, find employment, and marry, and are more likely to suffer from poor health, neurological symptoms, and psychiatric ailments, which interact with, or are exacerbated by, alcohol misuse.…”
mentioning
confidence: 99%